IMPLEMENTATION OF CITIZENSHIP VALUES THROUGH HEALTH EDUCATION TO THE COMMUNITY IN RT.25 - Subagya, Imelda Feylina (Unmul Civic Education Journal, 2022)
The background of writing research is to discuss (1) the influence of health education on the community. (2) implementation of citizenship values, especially in the health sector in the community. Education is an effort to help the souls of students or students both physically and mentally, things that must be considered and practiced in education are realizing, realizing, and doing. Education must refer to harmony between intentions, words, and actions. Health education is something that can influence a person for the creation of a healthy life. Health education is one of the educational activities that can be carried out by spreading messages to the public so that people are aware, know, understand, want and can take actions related to health. The purpose of this study is to determine the effect of health education on the community and how the implementation of the Pancasila values ​​of the community in the RT.25 environment affects health. Therefore, it is hoped that from this existing research it can be known what the effect of health on the community in the environment on the implementation of citizenship values ​​and the impact and solutions of problems that may exist.